Effects of on‐treatment ALT flares on serum HBsAg and HBV RNA in patients with chronic HBV infection. Issue 12 (28th September 2021) - Choi, Hannah S. J.; Sonneveld, Milan J.; Farag, Mina S.; Brouwer, Willem P.; Brakenhoff, Sylvia M.; Hirode, Grishma; Gehring, Adam J.; de Man, Rob A.; Hansen, Bettina E.; Janssen, Harry L. A.
Abstract: As pegylated interferon alpha (PEG‐IFN‐α) is increasingly used in combination regimens of novel drugs, we aimed to characterize ALT flares and their relationship with serum HBsAg and HBV RNA kinetics in a large combined cohort of chronic hepatitis B (CHB) patients on PEG‐IFN‐α‐based therapy. In this post hoc analysis of four international randomized trials, 269/130/124/128 patients on PEG‐IFN‐α monotherapy, PEG‐IFN‐α plus nucleos(t)ide analogue (NA) de novo combination, PEG‐IFN‐α add‐on to NA or NA monotherapy were included, respectively. A flare was defined as an episode of ALT ≥5 × ULN. The association between flares and HBsAg and HBV RNA changes were examined. On‐treatment flares occurred in 83/651 (13%) patients (median timing/magnitude: week 8 [IQR 4–12], 7.6 × ULN [IQR 6.2–10.5]). Flare patients were more often Caucasians with genotype A/D and had higher baseline ALT, HBV DNA, HBV RNA and HBsAg levels than the no‐flare group. More flares were observed on PEG‐IFN‐α monotherapy (18%) and PEG‐IFN+NA de novo combination (24%) vs. PEG‐IFN‐α add‐on (2%) or NA monotherapy (1%) ( p < .001). On‐treatment flares were significantly and independently associated with HBsAg and HBV RNA decline ≥1 log10 at the final visit declines started shortly before the flare, progressing towards 24 weeks thereafter. On‐treatment flares were seen in 16/22 (73%) patients who achieved HBsAg loss. In conclusion, ALT flares during PEG‐IFN‐α treatment are associated with subsequent HBsAg and HBV RNA decline and predict subsequent HBsAg loss. Flares rarely occurred during PEG‐IFN‐α add‐on therapy and associated with low HBsAg loss rates. Combination regimens targeting the window of heightened response could be promising.